MENINGKATKAN DAYA FIKIR KEWIRAUSAHAAN, PENGETAHUAN, KEPANDAIAN, INTELEKTUAL ATAU KOGNITIF DALAM AL-QUR’AN SURAT AL-FUSILAT AYAT 33 STUDI TAFSIR IBNU KATSIR - Adrianto, Adrianto; Haslinda, Haslinda; Sitorus, Cholid (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2025)
Abstract Have entrepreneurial intelligence such as (1) having the courage to take risks, (2) being able to recognize their strengths or potentials, where they have a clear vision in life, (3) having emotional intelligence good, (4) Always oriented to the process and results, (5) Adaptive to change, which is always willing to learn, change and develop following changes in markets and the environment, (6) Never stop innovating in the course of its business, (7) Able to always collaborate with other parties and work together positively with each other so that all parties can develop and succeed together - (8) Always build a business network (friendship) with partners and stakeholders related to their business, (9) Getting used to always provide benefits to the environment, sharing and advancing together so that they always have a positive spirit for success This study aims to describe Increasing Entrepreneurial Thinking Power Knowledge, Intelligence, Intellectual or Cognitive on Al-Qur’an al-Fussilat at 33 in tafsir of Ibnu Katsir the data collection technique is using library research or library study research with data collection techniques carried out by examining literature, document, and other sources of information related to the Topik of researchers. The result of this study the first, Khalifah who calls men to worship Allah and Increasing Entrepreneurial Thinking Power Knowledge, Intelligence, Intellectual or Cognitive on Al-Qur’an al Fussilat at 33 in tafsir of Ibnu Katsir is an obligation to all humans The second, Tafsir of Ibnu Katsir That All Knowledge Comes From Allah and Realization of Thinking and Behaving According to Values of Islam Is an Manifestation of Gratitude Towards Allah by making it happen entrepreneurship the point is independence (thoughts, skills, attitudes advanced mentality and intuition or vigilance, third, Responding to Business Competition on Syari’ah with rahmat of Allah namely with the principle of healthy competition that is, business people muslim does not justify any means; business people muslim strives to produce quality products and the best service on ayari’ah business people muslim have to pay attention of law islamic associated with contract of business